Labeling transparency and heavy metal contamination in commercial protein powders: A case study - Bavatharani V; Amrita Shaw; A. Sunil; Jhinuk Gupta (International Journal of Nutritions, 2026)
With the recent surge in market demand, health supplements particularly protein powders, have become increasingly vulnerable to quality deterioration, adulteration, and unethical marketing practices. Non-compliance with labeling regulations is on a rise. Moreover, research indicates that heavy metals absorbed from contaminated soil often accumulate in the protein fractions of crops, thereby elevating the risk of heavy metal contamination in protein powders. These issues highlight the urgent need to systematically assess both mislabeling and heavy metal contamination in commercially available protein powders. In this study, 110 protein powders, available in India, were manually screened to check their compliance with Food Safety and Standards Authority of India (FSSAI) regulations and six of those, containing maximum number of violations, were assessed for heavy metal contamination through Microwave Plasma – Atomic Emission Spectroscopy (MP-AES). Target Hazard Quotients (THQs) and Hazard Index (HI) values were calculated to assess potential health risks of the heavy metal contamination. The findings revealed widespread mislabeling. Around 25% products lacked “how to use” instructions, increasing the risk of excessive protein intake and protein poisoning. 30% products omitted mandatory warning statements and 42% failed to mention potential allergens. 75% of cocoa-based powder contained stevia, a sweetener regulated by FSSAI in cocoa based formulations. Additionally, 8% of the samples had incomplete ingredient lists. The MP-AES analysis revealed Arsenic to be the most abundant heavy metal present in the studied samples, followed by lead and mercury. The calculated Estimated Daily Intake (EDI) and Hazard Indices (HI) of all six protein powders revealed the severity of the health risk associated with the regular consumption of protein powders over a period of time. These findings highlight the critical need for stringent quality control measures in the dietary supplement industry and the implementation of sustainable strategies to prevent heavy metal contamination in protein powdersa
Keywords: Mislabeling, MP-AES; Protein powders; heavy metal contamination; market survey